Betaine supplementation affects carbohydrate metabolism in the skeletal muscle of finishing pigs - Gustavo de Amorim Rodrigues; Alysson Saraiva; Marcos Henrique Soares; Tiago Antônio Oliveira Mendes; Thais Correa Costa; Caroline Brito da Silva; Pedro Vieira Monteiro; Marcio Duarte (PLoS ONE, 2025)
This study aimed to assess the effect of betaine supplementation on the proteomic profile of the longissimus thoracis muscle in finishing pigs. Thirty-six crossbred female pigs (initial body weight = 88.96 ± 3.48 kg) were allocated in a completely randomized experimental design with two dietary treatments, with nine replications per treatment and two pigs per replication. The experimental diets consisted of a control diet (CON) and the CON diet supplemented with 2.5 g/kg of betaine (BET). At the end of the trial, one pig per unit was slaughtered, and longissimus thoracis (LT) muscle samples were analyzed via mass spectrometry to identify differentially abundant proteins (DAPs). Additionally, the intramuscular fat (IMF) content in the LT muscle was evaluated. Network analyses were performed to identify the biological processes and KEGG pathways. Results indicated that eleven DAPs were down-regulated (q-Value < 0.05) in the BET group compared to the CON group. Most DAPs were associated with carbohydrate metabolism, indicating that betaine may modulate cellular energy metabolism. These proteins were involved in glycolysis, glycogenolysis, the pentose phosphate pathway, and the glucagon signaling pathway. Moreover, pigs in the BET group had higher (P = 0.02) IMF compared to the CON group. In conclusion, betaine supplementation in finishing pigs down-regulated proteins related to carbohydrate metabolism in skeletal muscle, suppressed glucose metabolic processes and carbohydrate catabolic processes. These findings indicate alterations in glucose flow, possibly favoring other metabolic pathways, such as the pentose phosphate pathway. Furthermore, betaine supplementation increased IMF deposition and improved meat tenderness.